If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + -4x = 3x + 6 Reorder the terms: 27 + -4x = 6 + 3x Solving 27 + -4x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 27 + -4x + -3x = 6 + 3x + -3x Combine like terms: -4x + -3x = -7x 27 + -7x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 27 + -7x = 6 + 0 27 + -7x = 6 Add '-27' to each side of the equation. 27 + -27 + -7x = 6 + -27 Combine like terms: 27 + -27 = 0 0 + -7x = 6 + -27 -7x = 6 + -27 Combine like terms: 6 + -27 = -21 -7x = -21 Divide each side by '-7'. x = 3 Simplifying x = 3
| 81i^2= | | 8x-5=43 | | (3-9i)(4+9i)= | | x^2+18x-156=0 | | 9x-5=-139 | | x^2-14x=13 | | -3x+10y=-41 | | x(4y-9)+x(6-y)= | | (X^4-5x^2+4x)-(9x^3+x^2-2x+3)= | | 4n+10=5n | | -4x^2-9=-9 | | -3x+10(5)=16 | | 9x^2-20x+12=0 | | 6(x+2x)=2(3x+12) | | 3x-5(5)=16 | | -8x^3-44x^2=-32x-176 | | 0.8(2u-3)=(2u+4)0.6 | | 3x+5=-10+6x | | 150-3x=33x+18 | | -8-4x=10-10x | | 7x^3+49x^2= | | -4x^2-26x-4=0 | | x^3+3x+1=20 | | 10x^2+17x+4=0 | | 14-9x=139-44x | | -x^2+5x-3=0 | | -2x^2+x+7=0 | | 2(3.14)r=38.88 | | 4x^2+18x+10=0 | | 6x^2+36x-8=0 | | n^2+8n+15=0 | | 19x+13=51 |